Unexpected radiation pneumonitis after SIRT with significant decrease in DLCO with internal radiation exposure: a case report - TÜRELİ, DERYA; BALTACIOĞLU, FEYYAZ; ÖZGÜVEN, SALİH; KESİM, SELİN; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (BMC, 2020)
Background In the last years, Selective Internal Radiation Therapy (SIRT), using biocompatible Yttrium-90 (90Y) labeled microspheres have emerged for the treatment of malignant hepatic tumors. Unfortunately, a significant part of 90Y-labeled microspheres may shunt to the lungs after intraarterial injection. It can be predictable by infusing technetium-99 m-labeled macro-aggregated albumin particles through a catheter placed in the proper hepatic artery depending on the lobe to be treated with performing a quantitative lung scintigraphy. Radiation pneumonitis (RP) can occur 1 to 6 months after the therapy, which is a rare but severe complication of SIRT. Prompt timing of steroid treatment is important due to its high mortality rate. On the other hand, pulmonary diffusion capacity measured by carbon monoxide (DLCO) is an excellent way to measure the diffusing capacity because carbon monoxide is present in minimal amount in venous blood and binds to hemoglobin in the same manner as oxygen. Some authors reported that the most consistent changes after radiation therapy (RT) are recorded with this quantitative reproducible test. The relationship between the proportional reductions in DLCO and the severity of RP developing after this therapy may prove to be clinically significant. Case presentation We herein present a patient who developed RP after SIRT that could be quantified using DLCO. To the best of our knowledge, this case is the first who developed unexpected RP after SIRT with significant decrease in DLCO with internal radiation exposure. Conclusions RP is a very rare complication and may lead to a fatal outcome. Decline in DLCO could be a valuable parameter for follow-up and to identify potential candidates for RP and could be also another trigger for administration of steroid therapy with prompt timing in this patient group.
Keywords: Selective internal radiation therapy; Radiation induced pneumonitis; Diffusion capacity of the lungs for carbon monoxide; Y-90 MICROSPHERES; RADIOTHERAPY